Regulation, diversity and function of MECP2 exon and 3′UTR isoforms. (18th July 2020) - Rodrigues, Deivid Carvalho; Mufteev, Marat; Ellis, James
Abstract: The methyl-CpG-binding protein 2 ( MECP2 ) is a critical global regulator of gene expression. Mutations in MECP2 cause neurodevelopmental disorders including Rett syndrome (RTT). MECP2 exon 2 is spliced into two alternative messenger ribonucleic acid (mRNA) isoforms encoding MECP2-E1 or MECP2-E2 protein isoforms that differ in their N-termini. MECP2-E2, isolated first, was used to define the general roles of MECP2 in methyl-deoxyribonucleic acid (DNA) binding, targeting of transcriptional regulatory complexes, and its disease-causing impact in RTT. It was later found that MECP2-E1 is the most abundant isoform in the brain and its exon 1 is also mutated in RTT. MECP2 transcripts undergo alternative polyadenylation generating mRNAs with four possible 3′untranslated region (UTR) lengths ranging from 130 to 8600 nt. Together, the exon and 3′UTR isoforms display remarkable abundance disparity across cell types and tissues during development. These findings indicate discrete means of regulation and suggest that protein isoforms perform non-overlapping roles. Multiple regulatory programs have been explored to explain these disparities. DNA methylation patterns of the MECP2 promoter and first intron impact MECP2-E1 and E2 isoform levels. Networks of microRNAs and RNA-binding proteins also post-transcriptionally regulate the stability and translation efficiency of MECP2 3′UTR isoforms. Finally, distinctions in biophysical properties in the N-termini between MECP2-E1 and E2 lead to variable protein stabilities and DNA binding dynamics. This review describes the steps taken from the discovery of MECP2, the description of its key functions, and its association with RTT, to the emergence of evidence revealing how MECP2 isoforms are differentially regulated at the transcriptional, post-transcriptional and post-translational levels.